Formatting and document processing - VanHuss, Susie H. (Thomson South-Western Pub., 2008)
Welcome to Keyboarding Pro. Know Your Computer. Level 1: DEVELOPING KEYBOARDING SKILL. Module 1. Alphabetic Keys. Module 2. Figure and Symbol Keys. Communication Skills. Internet Activities. Appendix. Windows and Vista Basics. File Management Basics. Index